2018
DOI: 10.1101/400143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of green seaweed extract onArabidopsisearly development suggest roles for hormone signalling in plant responses to algal fertilisers

Abstract: The growing population requires sustainable, environmentally-friendly crops. The plant growthenhancing properties of algal extracts have suggested their use as biofertilisers. The mechanism(s) by which algal extracts affect plant growth are unknown.We examined the effects of extracts from the common green seaweed Ulva intestinalis on germination and root development in the model land plant Arabidopsis thaliana. Ulva extract concentrations above 0.1% inhibited Arabidopsis germination and root growth. Ulva extra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 108 publications
(121 reference statements)
0
8
0
Order By: Relevance
“…The nutrient analysis of freshwater macroalga showed the presence of macroelements, Ca, K, Mg and Na, as well as microelements such as Cu, Mn, Zn, etc. This content was much higher than for other green seaweed, for example, Ulva lactuca , collected from the coastal area of Jalisco, Mexico (Na 77.7 mg/kg, K 18.5 mg/kg, Ca 18.8 mg/kg, and P 1 mg/kg) and for Ulva intestinalis from the coastal area of Llantwit Major beach, South Wales, where the content of Ca was 37 046 mg/kg and of K 16 466 mg/kg . The content of Mg and Na in Ulva intestinalis in the work of Ghaderiardakani et al.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…The nutrient analysis of freshwater macroalga showed the presence of macroelements, Ca, K, Mg and Na, as well as microelements such as Cu, Mn, Zn, etc. This content was much higher than for other green seaweed, for example, Ulva lactuca , collected from the coastal area of Jalisco, Mexico (Na 77.7 mg/kg, K 18.5 mg/kg, Ca 18.8 mg/kg, and P 1 mg/kg) and for Ulva intestinalis from the coastal area of Llantwit Major beach, South Wales, where the content of Ca was 37 046 mg/kg and of K 16 466 mg/kg . The content of Mg and Na in Ulva intestinalis in the work of Ghaderiardakani et al.…”
Section: Resultsmentioning
confidence: 80%
“…The content of Mg and Na in Ulva intestinalis in the work of Ghaderiardakani et al. (2019) was much higher (Mg 14 291 mg/kg and Na 61 861 mg/kg; these two elements dominate in the composition of marine water) than for the tested freshwater C. glomerata . Freshwater macroalga can be recommended as a raw material for the production of biostimulants of plant growth.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sugars for instance act both as effective signalling molecules and as immediate substrates for intermediary metabolism, and could therefore promote plant growth and development 20,23 . A role for macro-and microelements, vitamins and phytohormones in alga extracts may also be suggested 11,12,20,24 . For instance 16 , reported that Potassium in seaweed extracts have a positive effect on regulating water status in treated plants and enhancing photosynthesis and meristematic growth.…”
Section: Discussionmentioning
confidence: 99%